Transvenous neurostimulation for central sleep apnoea: a randomised controlled trial. Issue 10048 (3rd September 2016) - Costanzo, Maria Rosa; Ponikowski, Piotr; Javaheri, Shahrokh; Augostini, Ralph; Goldberg, Lee; Holcomb, Richard; Kao, Andrew; Khayat, Rami N; Oldenburg, Olaf; Stellbrink, Christoph; Abraham, William T; ,
Summary: Background: Central sleep apnoea is a serious breathing disorder associated with poor outcomes. The remedé system (Respicardia Inc, Minnetonka, MN, USA) is an implantable device which transvenously stimulates a nerve causing diaphragmatic contraction similar to normal breathing. We evaluated the safety and effectiveness of unilateral neurostimulation in patients with central sleep apnoea. Methods: We recruited patients from 31 hospital-based centres in Germany, Poland, and the USA in this prospective, multicentre, randomised trial. Participants had to have been medically stable for at least 30 days and have received appropriate guideline recommended therapy, be aged at least 18 years, be expected to tolerate study procedures, and willing and able to comply with study requirements. Eligible patients with an apnoea-hypopnoea index (AHI) of at least 20 events per h, tested by a polysomnography, underwent device implantation and were randomly assigned (1:1) by a computer-generated method stratified by site to either stimulation (treatment) or no stimulation (control) for 6 months. The primary effectiveness endpoint in the intention-to-treat population was the comparison of the proportions of patients in the treatment versus control groups achieving a 50% or greater AHI reduction from baseline to 6 months, measured by a full-night polysomnography assessed by masked investigators in a core laboratory. The primary safety endpoint of 12-month freedom from serious adverse events related to the procedure, system, or therapy was evaluated in all patients. This trial is active, but not recruiting, and is registered withClinicalTrials.gov (NCT01816776 ). Findings: Between April 17, 2013, and May 28, 2015, we randomly assigned 151 eligible patients to the treatment (n=73) or control (n=78) groups. In the analysis of the intention-to-treat population, significantly more patients in the treatment group (35 [51%] of 68) had an AHI reduction from baseline of 50% or greater at 6 months than had those in the control group (eight [11%] of 73; difference between groups 41%, 95% CI 25–54, p<0·0001). 138 (91%) of 151 patients had no serious-related adverse events at 12 months. Seven (9%) cases of related-serious adverse events occurred in the control group and six (8%) cases were reported in the treatment group. Seven patients died (unrelated to implant, system, or therapy), four deaths (two in treatment group and two in control group) during the 6-month randomisation period when neurostimulation was delivered to only the treatment group and was off in the control group, and three deaths between 6 months and 12 months of follow-up when all patients received neurostimulation. 27 (37%) of 73 patients in the treatment group reported non-serious therapy-related discomfort that was resolved with simple system reprogramming in 26 (36%) patients, but was unresolved in one (1%) patient. Interpretation: Transvenous neurostimulation significantly reduced the severity of central sleep apnoea, including improvements in sleep metrics, and was well tolerated. The clinically meaningful effects of the therapy are supported by the concordant improvements in oxygenation and quality of life, making transvenous neurostimulation a promising therapeutic approach for central sleep apnoea. Funding: Respicardia Inc.